A Comparative Analysis of "Jawab e Shikwa": A Vinay and Darbelnet Model-based Examination of Two English Translations - Edi Suprayetno; Malik Umer Ajmal; Marina Khan (Journal of Applied Linguistics, 2024)
This research explored the translation of the Urdu poem "Jawab-e-Shikwa" by Muhammad Iqbal into English, focusing on two versions by Altaf Hussain and Frances W. Pritchett. The study employed the Vinay and Darbelnet model to analyze translation strategies such as equivalence, modulation, and oblique translation. The analysis revealed differences in linguistic accuracy, cultural relevance, and literary style between the two translations. Through a qualitative and quantitative approach, the study aimed to provide a comprehensive understanding of the impact of translation on the interpretation of "Jawab-e-Shikwa" in both Urdu and English-speaking contexts. From the Result of the analysis it was found that Hussain employed an oblique translation approach with techniques such as equivalence and modulation, capturing the essence of the original poem with a sense-for-sense translation. Pritchett, on the other hand, adopted a direct translation strategy, offering a word-for-word rendition that maintains clarity but may lack the nuanced impact of the Urdu original. Both translations effectively conveyed the overall meaning of the poem, Hussain's version demonstrated a greater adherence to the cultural and literary nuances of the original Urdu, providing a more intricate and contextually rich interpretation. Pritchett's literal approach, while clear and accurate, may compromise the poetic and cultural depth inherent in Iqbal's work. Keywords : Jawab e Shikwa; Vinay and Derbelnet model; Translation Technique